Which first step for solving the given system using substitution results in an equation without fractions?

[3x+y=9

15x-3y = 1

Solve for x in the first equation.

Solve for y in the first equation.

Solve for x in the second equation.

Solve for y in the second equation.

Respuesta :

Answer:

Solve for y in the first equation.

Step-by-step explanation:

Given

3x+y=9

15x-3y = 1

Required

Determine the first step to avoid fractions

From the list of given options, the option that best answered the question is to Solve for y in the first equation.

Solving for y will let you substitute the expression for y in the second equation

Going by that:- Solve for y in the first equation.

[tex]3x + y = 9[/tex]

Subtract 3x from both sides

[tex]3x - 3x + y = 9 - 3x[/tex]

[tex]y = 9 - 3x[/tex]

Substitute 9 - 3x for y in the second equation

[tex]15x - 3y = 1[/tex] becomes

[tex]15x - 3(9 - 3x) = 1[/tex]

[tex]15x - 27 + 9x = 1[/tex]

Collect like terms

[tex]15x + 9x = 1 + 27[/tex]

[tex]24x = 28[/tex]

Divide both sides by 24

[tex]\frac{24x}{24} = \frac{28}{24}[/tex]

[tex]x = \frac{28}{24}[/tex]

Divide numerator and denominator by 4

[tex]x = \frac{7}{6}[/tex]

Substitute 7/6 for x in the [tex]y = 9 - 3x[/tex]

[tex]y = 9 - 3 * \frac{7}{6}[/tex]

[tex]y = 9 - \frac{7}{2}[/tex]

Solve fraction

[tex]y = \frac{18-7}{2}[/tex]

[tex]y = \frac{11}{2}[/tex]

Answer:

It's B (the one above is right)

Step-by-step explanation:

ACCESS MORE